Nutrition related non-communicable diseases and sugar sweetened beverage policies: a landscape analysis in Zambia - Mulenga M. Mukanu; Safura Abdool Karim; Karen Hofman; Agnes Erzse; Anne-Marie Thow (Taylor & Francis Group, 2021)
Background: Taxation on unhealthy products is recommended as a cost-effective intervention to address the global burden of non-communicable diseases. Taxation of sugar-sweetened beverages dis-incentivize consumption of unhealthy products. Implementation of such policies is difficult in Sub-Saharan African countries, which are targets for global corporate expansion by the sugar-sweetened beverages industry. Objective: To identify opportunities to strengthen policies relating to sugar-sweetened beverage taxation in Zambia, through: (1) understanding the policy landscape and political context in which policies for nutrition-related non-communicable diseases are being developed, particularly sugar-sweetened beverage taxation, and exploring the potential use of revenue arising from sugar-sweetened beverage taxation to support improved nutrition. Methods: We conducted a retrospective qualitative policy analysis with a review of nutrition-related non-communicable diseases policies and key informant interviews (n = 10) with policy actors. Data were coded and analyzed data using pre-constructed matrices based on the Kingdon's Policy Agenda Framework. Results: Government responses to nutrition-related non-communicable diseases were developed in an incoherent policy environment. The health sector's commitment to regulate sugar-sweetened beverages conflicted with the manufacturing sector's priorities for economic growth. Increased regulation of sugar-sweetened beverages was a priority for the health sector. Economic interests sought to grow the manufacturing sector, including the food and beverage industries. Consequently, incoherent policy objectives might have contributed to the adoption of a weakened excise tax. The general public were poorly informed about nutrition-related non-communicable diseases. Conclusions: The tension between the Government's economic and public health priorities is a barrier for strengthening fiscal measures to address nutrition-related non-communicable diseases. However, this did not prevent the introduction of a differential sugar tax on sugar-sweetened beverages. Opportunities exist to strengthen the existing taxation of sugar-sweetened beverages in Zambia. These include a more inclusive consultation process for policy formulation and comprehensive monitoring of risk factors.